Unlocking the medicinal arsenal of Cissus assamica: GC‐MS/MS, FTIR, and molecular docking insights - Mohammad Abdullah Taher; Ripa Kundu; Aysha Akter Laboni; Suriya Akter Shompa; Md. Moniruzzaman; Mohammad Mahmudul Hasan; Hasin Hasnat; Md. Mehedi Hasan; Mala Khan (Health Science Reports, 2024)
Abstract Background and aims This study investigated the biochemical components present in the leaves of Cissus assamica. The primary aim was to analyze these components using advanced techniques and assess their potential therapeutic applications. Methodology Fourier Transform Infrared (FT‐IR) spectroscopy, Gas Chromatography‐Mass Spectrometry (GC‐MS), and Mass Spectral analysis were employed to identify and characterize the compounds in Cissus assamica leaves. The mass spectra of each compound were compared with data from the Wiley and NIST libraries to determine their names, molecular masses, and chemical structures. FT‐IR analysis identified characteristic functional groups by their specific frequencies. Results and discussion FT‐IR spectroscopic analysis revealed significant molecular vibrations at frequencies of 3265.63, 2853.81, 1638.60, 1469.21, and 1384.95 cm⁻¹, indicating the presence of specific functional groups. The GC‐MS analysis identified distinct compounds, such as “aR‐Turmerone,” “Curlone,” “7,8‐Epoxylanostan‐11‐ol, 3‐acetoxy‐,” “13‐Docosenamide, (Z)‐,” “Phenol, 3,5‐bis(1,1‐dimethylethyl)‐,” “9,19‐Cyclolanostan‐3‐ol, 24,24‐epoxymethano‐, acetate,” and “Quinoline‐5,8‐dione‐6‐ol, 7‐[[(4‐cyclohexylbutyl)amino]methyl]‐.” These compounds exhibited potential therapeutic applications. Their cytotoxic, antimicrobial, antidiarrheal, anti‐hyperglycemic, and pain‐relieving properties were evaluated by comparing them with reference ligands targeting specific receptors, including dihydrofolate reductase (DHFR), epidermal growth factor receptor (EGFR), kappa opioid receptor (KOR), glucose transporter 3 (GLUT 3), and cyclooxygenase 2 (COX‐2). Conclusion The results of this study suggest that Cissus assamica leaves contain bioactive compounds with potential therapeutic benefits for treating infections, diarrhea, hyperglycemia, and pain. However, further research is needed to conduct comprehensive phytochemical screening and establish the precise mechanisms of action for the crude extract or the plant‐derived compounds.